Pengaruh Pengembangan Karir dan Kompensasi terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan Kantor PT. REA Kaltim Cabang Samarinda) (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this research was to examine the effect of Career Development and Compensation on Employee Performance PT Office. Rea Kaltim Samarinda Branch. The collection of research data using saturated sample. The sample used in this research that the entire population of 70 respondents employees of PT. Rea Kaltim samarinda branch. This study used multiple linear regression analysis with SPSS as an instrument to calculate the data. The results showed that there is significant influence between career development on employee performance. And there is significant influence between the compensation the employee performanceKeywords: career development, compensation, performance